How to answer the question Does sexual offender treatment work? - Marques, Janice K. (Journal of interpersonal violence, 1999)
Although sex offender treatment is an established clinical specialty, evidence regarding its effectiveness has been slow to accumulate. One ongoing treatment outcome study, California's Sex offender Treatment and Evaluation Project (SOTEP), is used to highlight several problems that are inherent in this type of research, and to illustrate that even well-designed studies make only a limited contribution to our empirical database on treatment effectiveness. SOTEP findings are also used to show that the broad question, "Does sex offender treatment work?" needs to be broken down into a number of more specific and useful questions. Given the diversity of clients and programs in this field, outcome data are from a wide range of treatment programs that vary in approach, setting, intensity, and types of offenders treated. Program managers and clinicians are urged to evaluate the impact of their services in order to contribute to our knowledge base on treatment effectiveness